2020
DOI: 10.1001/jamaneurol.2020.0851
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Rituximab Treatment for New-Onset Generalized Myasthenia Gravis and Refractory Generalized Myasthenia Gravis

Abstract: IMPORTANCE Use of biologic agents in generalized myasthenia gravis is generally limited to therapy-refractory cases; benefit in new-onset disease is unknown. OBJECTIVE To assess rituximab in refractory and new-onset generalized myasthenia gravis and rituximab vs conventional immunotherapy in new-onset disease. DESIGN, SETTING, AND PARTICIPANTSA retrospective cohort study with prospectively collected data was conducted on a county-based community sample at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 41 publications
(79 reference statements)
6
80
0
Order By: Relevance
“…Rituximab has a role in patients presenting aggressively and explosively at onset and who are refractory to all conventional therapies. Brauner et al (114) demonstrated that clinical outcomes were better in patients who were treated early rather than later with Rituximab. There is scope for considering Rituximab in patients who are in crisis and who are not responding to high dose corticosteroids or ivIG or PE, and when patients demonstrate resistance in weaning off ventilation during the treatment pathway of MG crisis.…”
Section: The Refractory Mg Patient and Novel Therapiesmentioning
confidence: 99%
“…Rituximab has a role in patients presenting aggressively and explosively at onset and who are refractory to all conventional therapies. Brauner et al (114) demonstrated that clinical outcomes were better in patients who were treated early rather than later with Rituximab. There is scope for considering Rituximab in patients who are in crisis and who are not responding to high dose corticosteroids or ivIG or PE, and when patients demonstrate resistance in weaning off ventilation during the treatment pathway of MG crisis.…”
Section: The Refractory Mg Patient and Novel Therapiesmentioning
confidence: 99%
“…The most common MG evaluation scores are manual muscle testing (MMT), quantitative MG (QMG) score, MGFA-PIS, and MGCS. Due to the nature of our study, we used the MGCS, which evaluates only clinical parameters [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Remission was more frequent in MuSK positive patients than in AChRab positive patients (71 vs. 36%) ( 72 ). Another recent retrospective review from Stockholm showed that rituximab shortened the time to remission and the need for additional immunosuppressive therapies in patients with new-onset MG treated within 12 months after diagnosis, compared to the longer time for remission in those with refractory disease ( 73 ). The time to remission was shorter with rituximab compared to those who received other immunosuppressive therapy.…”
Section: Direct B Cell Depletorsmentioning
confidence: 99%